EFEK KEPEMIMPINAN TRANSFORMASIONAL TERHADAP SEMANGAT KERJA DAN KEPUASAN KERJA PT. PELABUHAN INDONESIA IV (PERSERO) MAKASSAR - , LESTARI, Dra. Supra Wimbarti, M.Sc., Ph.D., Psi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims at examining the effect of transformational leadership on work enthusiasm and job satisfaction in PT. Pelabuhan Indonesia IV (Persero) Makassar. The subject of this research were employees in the port of PT. Pelabuhan Indonesia IV (Persero) Makassar, comprised of 123 employees with minimum working period is two years and at the level of grade is 11 until 14. The data were collected by work enthusiasmâs scale, job satisfactionâs scale and transformational leadershipâs scale. The data were analized using Repeated Regression Analysis. The results shows that, first, there is significant influence of transformational leadershipâs variable to work enthusiasm with R = 0,359, p = 0.000 and determinant coefficient = 0,129, with inspirational aspect significantly influenced the work enthusiasm. Second, there is significant influence of transformational leadershipâs to job satisfaction with R = 0,651, p = 0.000 and determinant coefficient = 0,423. Intellectual stimulation aspect is significantly influenced the job satisfaction.